Innovation for unmet patient needs: multinational pharmaceutical companies deliver value to Malaysia through clinical trials / June Choon Wai Yee - Choon, June Wai Yee (Faculty of Pharmacy, 2024)
In the realm of medical innovation and patient care, Malaysia has achieved remarkable milestones in the clinical research landscape. As an invited delegate at the Clinical Trial Connect 2024 held on May 9 & 10, I witnessed the nation's impressive strides; a recordbreaking 276 newly sponsored clinical research studies brought in RM 1.16 billion in cumulative gross national income and created 2753 skilled jobs in clinical research since 2012. Surpassing its targets and previous years' accomplishments, Malaysia stands tall as a frontrunner in clinical trials within the Southeast Asia region, having secured second place in the number of global industry-sponsored studies.